A study on human error in the interaction with the computer systems - Begosso, Luiz Carlos; Silva, Maria Alice Siqueira Mendes [UNESP]; Cortez, Thiago Henrique (Springer Nature, 2011)
The term human factor is used by professionals of various fields meant for understanding the behavior of human beings at work. The human being, while developing a cooperative activity with a computer system, is subject to cause an undesirable situation in his/her task. This paper starts from the principle that human errors may be considered as a cause or factor contributing to a series of accidents and incidents in many diversified fields in which human beings interact with automated systems. We propose a simulator of performance in error with potentiality to assist the Human Computer Interaction (HCI) project manager in the construction of the critical systems. © 2011 Springer-Verlag.
Keywords: Computer Systems; Human Computer-Interaction; Human Error; Simulator of Performance in Error; Automated systems; Cooperative activity; Critical systems; Human being; Human errors; Project managers; Automation; Behavioral research; Errors; Human engineering; Knowledge management; Project management; Human computer interaction